Unpacking Post-Haiyan Disaster Resettlement Narratives of Young Filipino Women Informal Settlers in Tacloban City, Philippines: A Spatial Narrative Approach - Espina, Ervina (Archīum Ateneo, 2019)
Post‐disaster resettlement narratives encapsulate the complex mobile–spatial processes that are embedded in a post‐disaster context. The existing literature on disaster relocation and resettlement accords primacy to the logistical, practical, structural, and physical dimensions of residential transitioning. Building on this knowledge, this study conducted a spatial narrative inquiry to generate a link to mobile–spatial realities interspersed in diverse temporal trajectories. It did so by tracking the embodied rhythms of people and objects evoked through the retelling of post‐disaster resettlement stories by 12 young Filipino women informal settlers. The key findings are organised in three spatial narratives: ‘house near the sea'; ‘there at the bunkhouse'; and ‘here in Ridgeview'. These narratives are anchored in the overarching dimensions that underpin Filipino informal settlers’ experiences of (not) moving in and out of disaster resettlement areas. Lastly, the findings are explained in the light of the theoretical, empirical, and practical implications of disaster resettlement specific to informal settlers.